2017
DOI: 10.1038/s41598-017-15152-8
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and epidemiological characterisation of a dengue virus outbreak among blood donors in Brazil

Abstract: Outbreaks caused by Dengue, Zika and Chikungunya viruses can spread rapidly in immunologically naïve populations. By analysing 92 newly generated viral genome sequences from blood donors and recipients, we assess the dynamics of dengue virus serotype 4 during the 2012 outbreak in Rio de Janeiro. Phylogenetic analysis indicates that the outbreak was caused by genotype II, although two isolates of genotype I were also detected for the first time in Rio de Janeiro. Evolutionary analysis and modelling estimates ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 71 publications
(83 reference statements)
4
38
0
Order By: Relevance
“…Model output on cumulative death counts ( ) is fitted to the reported time series of deaths Λ (see Data) using a Bayesian MCMC approach previously implemented in other modelling studies [7][8][9][10] . Model variables are summarized in probability of dying with severe disease θ Gaussian distribution G(M=0.14, SD=0.007) [1,2,11,17] proportion of population at risk of severe disease ρ Gamma distribution G1(S=5, R=5/0.01), G2(S=5, R=5/0.001) --population size N UK 66.87M, Italy 60M ---…”
Section: Modelmentioning
confidence: 99%
“…Model output on cumulative death counts ( ) is fitted to the reported time series of deaths Λ (see Data) using a Bayesian MCMC approach previously implemented in other modelling studies [7][8][9][10] . Model variables are summarized in probability of dying with severe disease θ Gaussian distribution G(M=0.14, SD=0.007) [1,2,11,17] proportion of population at risk of severe disease ρ Gamma distribution G1(S=5, R=5/0.01), G2(S=5, R=5/0.001) --population size N UK 66.87M, Italy 60M ---…”
Section: Modelmentioning
confidence: 99%
“…Recife is located in the state of Pernambuco in the north-east of Brazil with a tropical savanna climate, while São Paulo is located in the south with a humid subtropical climate (Köppen climate classification (Peel, Finlayson, & McMahon, 2007 DENV and CHIKV (de Araújo et al, 2016;Magalhaes et al, 2017;Sabino et al, 2016). In contrast, São Paulo is yet to experience a sustained ZIKV epidemic, DENV incidence is known to be low for the national average (Teixeira, Siqueira, Ferreira, Bricks, & Joint, 2013) and transmission of mosquito-borne viruses is unstable, with phylogenetic studies showing that epidemics are seeded by new lineages almost every year (Faria et al, 2017a(Faria et al, ,2017b. In the notified dengue data that we obtained for 2007-2012 (See Data accessibility3), the total incidence per 100k individuals in Recife was approximately 11fold higher than it was in São Paulo (2184.3 notifications vs. 195.2).…”
Section: Index P Dynamics In Recife and São Paulomentioning
confidence: 99%
“…Phylogenetic analyses can reveal a better picture of arboviral outbreak, as have been occurred in Brazil in CHIKV outbreak. Phylogenetic reconstruction suggests several separate introductions of the Asian genotype (ECSA) strain, in contrast to a unique introduction of the ECSA genotype followed by virus dissemination inside the country also in DENV outbreaks . In CHIKV Italian outbreak in September 2017, phylodynamic analysis showed that the virus was in loco at least 3 months before the outbreak and, in particular, it probably originated in Pakistan and not India as the classical epidemiology supposed …”
Section: Phylogenesis and Phylodynamic Of Arbovirusesmentioning
confidence: 99%
“…171,172 The comparison of HIV-1 intrahost genealogies from patients sampled under different conditions could help in understanding the viral reservoir dynamics, the most important knowledge for the HIV- Phylogenetic reconstruction suggests several separate introductions of the Asian genotype (ECSA) strain, in contrast to a unique introduction of the ECSA genotype followed by virus dissemination inside the country 174,175 also in DENV outbreaks. 176 In CHIKV Italian outbreak in September 2017, phylodynamic analysis showed that the virus was in loco at least 3 months before the outbreak and, in particular, it probably originated in Pakistan and not India as the classical epidemiology supposed. 177 As well as in ZIKV outbreaks, phylogenetic inference showed how the outbreak in Brazil was closely related to the French Polynesia isolates that circulated in November 2013 35,178 and that all viruses The application of Bayesian statistical inference framework, can allow the reconstruction of the geographic history of the still ongoing and never reported before epidemic on the basis of the first isolates sampled at known times.…”
Section: The Phylogeny Of Genotypes B and Cmentioning
confidence: 99%